ACCOUNTING METHODS FOR FINANCIAL REPORTING PURPOSES: NATIONAL AND INTERNATIONAL ASPECTS - FRANCHUK, Iryna; MUZYCHENKO, Andrii; SKRYPNYK, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines accounting methods for the purpose of financial reporting using the example of national and global application of rules and standards. General research methods were used: analysis, synthesis, comparison and grouping, schematic display of results. The research methodology takes into account a generalization of domestic and foreign features of accounting methods and methods for preparing financial statements, scientific analysis of standards of accounting methods, fundamental provisions of economic theory, accounting and reporting. A comparison of accounting approaches according to NP(S)BU 1 "General Requirements for Financial Reporting" and International Financial Reporting Standards IAS 1 "Presentation of Financial Statements" was carried out to assess the state of national accounting methods with world practice. Separate measures are proposed to systematize methods for preparing financial statements. The need to take into account the characteristics and essence of individual species using the modeling method is substantiated, which will allow generating reporting in conditions close to international standards. The results of the study can be useful for further approximation of the conditions and features of the application of accounting and reporting methods according to national to international standards. The study analyzed and summarized the state of regulatory regulation of the application of accounting methods for the preparation of financial statements, taking into account national and international aspects. It has been determined that the accounting method is a system of interrelated methods and techniques for displaying the value of objects. Accounting methods are general scientific and specific, and it is the latter that are the object of regulatory regulation at both the national and international levels. It is noted that national accounting standards should take into account all methods that contribute to the preparation of financial statements close to international standards. For the current state of accounting science and practice, taking into account the achievements of foreign standards of accounting and reporting, the most practical direction of improving methods is the use of the modeling method. The issues of accounting and reporting need further study through the prism of the elements of the accounting method reflected in the accounting policy.